Neurotrophic Activity of Cultured Cell Line U87 is Up-Regulated by Proline-Rich Polypeptide Complex and Its Constituent Nonapeptide - Zabłocka, Agnieszka (Cell Mol Neurobiol, 2015)
Neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor, as well as cytokines, for example, interleukin-6 (IL-6) play an important role in neuroprotection and in the control of the central nervous system (CNS) function. Reduced expression of neurotrophic factors can lead to dysregulation of neuron function and neuronal death. There is also evidence for mutual interactions between neurotrophins and IL-6. Therefore, the up-regulating the level of neuroprotective substances is one of the key manners to control the nervous system development and function. It can be a promising aim in the therapy of neurodegenerative disease in which the decreased level of neurotrophins is observed. In our recent studies, the role of proline-rich polypeptide complex (PRP) and its nonapeptide fragment (NP) in the regulation of neurotrophic activity in cultured astrocytes was shown. PRP and NP stimulate human astrocytoma cell line U87 to release the significant amounts of NGF to the extracellular space both in its precursor and mature form. We also provide the evidence that in NP-treated cells, the level of βNGF mRNA was increased. NP-treated cells used in this study produced also increasing amounts of IL-6. This finding indicates that PRP and its nonapeptide fragment NP up-regulate neurotrophic activity of U87 cell line by increase of NGF synthesis and its release into the extracellular space. It was also shown that NP-dependent increased production of IL-6 can enhance the NGF activity.